Óleo de linhaça na dieta de fêmeas e machos castrados Nelore x Canchim, terminados em confinamento - Rosa, Bruna Laurindo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The objective was to evaluate the effect of diets containing levels of linseed oil in the performance, carcass characteristics, weight, yield of cuts of meat, and meat quality of heifers and steers Nellore x Canchim. Fifteen 24-monthold steers (427.80 ± 40.59 kg) and fourteen 24-month-old heifers (400.57 ± 32.57 kg, average body weight) were confined in individual pens, receiving diets with 80% of concentrated, sugar cane as exclusive roughage and increasing levels of linseed oil (1.0, 3.8 and 5.2% on a DM basis). The experiment was designed in an incomplete random blocks one, in a factorial scheme of 3 x 2 (type of diet and sexual condition). The initial weight of animals was used as co-variable and the blocks were considered as the randomizing effect. All of the animals of every block were slaughtered once they reached an average body weight of 500 kg; this resulted in 96 days of feedlot for two blocks, 110 days for other two blocks and 138 days for one block, after 28 days of adaptation. Dry matter consumption by animals, in kg and body weight percentage, was reduced (P<0.05), accompanied with higher daily weight gains, an improvement in feed efficiency and an increase in the Longissimus eye area in the carcass with an elevation of oil levels in diets, without differences between sex conditions. The backfat thickness increased with higher linseed oil levels on the diet and results differed between sex conditions, with higher values for heifers (12.17 mm) in relation to steers (8.58 mm). The weight of meat cuts such as the shoulder clod, complete top sirloin butt (top sirloin butt + top sirloin cap + bottom sirloin butt), strip loin and top round, as well as the sum of the noble meat cuts (top sirloin butt + strip loin + full tenderloin), less noble meat cuts (chuck roll + chuck mock tender + shoulder clod + fore shank and shank + hump + point half brisket + neck + outside round), barbecue ...

Objetivou-se com este trabalho avaliar dietas contendo teores de óleo de linhaça sobre o desempenho, as características da carcaça, o peso, o rendimento de cortes cárneos, e a qualidade da carne de fêmeas e machos castrados Nelore x Canchim. Quinze machos castrados (427,80 ± 40,59 kg) e 14 fêmeas (400,57 ± 32,57 kg, em média de peso corporal), com 24 meses de idade foram confinados, recebendo dietas com 80% de concentrado, cana-de-açúcar como volumoso exclusivo e teores crescentes de óleo de linhaça (1,0; 3,8 e 5,2% da MS). O delineamento experimental foi em blocos incompletos ao acaso, em esquema fatorial 3 x 2 (dietas e condição sexual), sendo o peso inicial dos animais utilizado como covariável e os blocos como efeito aleatório. Todos os animais de cada bloco foram abatidos quando o peso corporal médio atingiu 500 kg; assim, o tempo de confinamento foi de 96 dias para dois blocos, 110 dias para dois blocos e 138 dias para um bloco, após 28 dias de adaptação. O consumo de matéria seca pelos animais, em kg/dia e % do peso corporal, foi reduzido (P<0,05), acompanhado de maiores ganhos de peso, melhora da eficiência alimentar e aumento da área de olho de lombo na carcaça com a elevação dos teores de óleo nas dietas, sem diferenças entre as condições sexuais; a espessura de gordura de cobertura na carcaça foi crescente com o aumento dos teores de óleo de linhaça na dieta e diferiu entre as condições sexuais, com maiores valores para as fêmeas (12,17 mm) em relação aos macho castrados (8,58 mm). Os pesos dos cortes da paleta, alcatra completa (alcatra + picanha + maminha), contrafilé e coxão mole, e as somatórias dos cortes nobres (alcatra completa + contrafilé + filé mignon), de segunda (acém + peixinho + paleta + músculos do dianteiro e traseiro + cupim + ponta de peito + pescoço + coxão duro), para churrasco ...
Keywords: Bovino; Bovino - Alimentação e rações; Carne - Cortes; Eficiencia alimentar; Confinamento (Animais); Meat cuts